Suggested Solutions to Recidivism by Prison Officers in Kwara State, Nigeria - Adegboyega, Lateef Omotosho; Idowu, Oluwasola Opeyemi; Idowu, Adeyemi Ibukunoluwa (Universitas Negeri Semarang, 2019)
Recidivism is a growing problem in the world – in Nigeria and Kwara State inclusive. Therefore, this study investigated solutions to recidivism as perceived by prison officers in Kwara State. The contributions of moderating variables of gender, religion and years in service were also investigated. Descriptive research design was adopted for the study. The population comprised all the prison officers estimated at 615 in Kwara State. Multi-stage sampling procedure was adopted to select 250 prison officers from all the five prison centers in Kwara State. A questionnaire that was designed by the researchers served as the instrument for data collection. The validity and reliability of the instrument were duly established. The data were analysed using percentages, t-test and Analysis of Variance (ANOVA). Hypotheses were tested at 0.05 level of significance. Findings revealed that recidivism rate will be drastically reduced if prison rehabilitation programmes are being handled by professionally trained rehabilitation counsellor, if ex-convicts are assisted to utilize the entrepreneurial skills acquired in prison, and if there is a periodic evaluation of prison reformation and rehabilitation programme to ensure that the goals are being achieved. The findings further revealed significant differences in solutions to recidivism as perceived by Prison Officers in Kwara State based on religion and years in service but no significant difference was found based on gender. The findings imply that counsellors need to beam their searchlight into issues of crime, imprisonment and recidivism; counselors in-training need to be trained on strategies for rendering rehabilitation services to prison inmates.